If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4x + -8 = 2x + 16 Reorder the terms: -8 + -4x = 2x + 16 Reorder the terms: -8 + -4x = 16 + 2x Solving -8 + -4x = 16 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -8 + -4x + -2x = 16 + 2x + -2x Combine like terms: -4x + -2x = -6x -8 + -6x = 16 + 2x + -2x Combine like terms: 2x + -2x = 0 -8 + -6x = 16 + 0 -8 + -6x = 16 Add '8' to each side of the equation. -8 + 8 + -6x = 16 + 8 Combine like terms: -8 + 8 = 0 0 + -6x = 16 + 8 -6x = 16 + 8 Combine like terms: 16 + 8 = 24 -6x = 24 Divide each side by '-6'. x = -4 Simplifying x = -4
| (7-w)(4w+6)=0 | | (x+50)=x | | 0.50x+0.25(30)=29.5 | | x=(x+50) | | 2x+6y=248 | | 0=154-10t-16t^2 | | 8x+6=8-(7x-4) | | 3(x-2)+4x=36 | | 4x+3=5-(5x-9) | | 4(3x+5)=43 | | 22x^2-21xy+5y^2= | | 8-6(2-2x)=0 | | 3x+22=3+8x-6 | | C=43+-0.5m | | 12x+16=6-4x | | 7-2(5x+8)=9 | | 4w^2=11w-6 | | x+2x(2x+5)=100 | | (2v-7)(3-v)=0 | | 4c+2m=172 | | 9.1=m*91 | | 5x+5=5(x-8) | | 2/5(4x+11)=3(1-2x)+9 | | 6X1/12 | | (-3/5x+5)=(x/5x+5) | | 3/x+3=5/4x+25/8 | | F(-3)=-3x^3-2 | | F(x)=-3x^3-2 | | 1/5(2x+11) | | (2p-2/p)*(5p^2/6p-6) | | (5w-1)(6+w)=0 | | 4/3(1+6x)-1/4(30x-2/3)=5 |